A high-density heavy medium suspension and preparation method

Through a high-density heavy medium suspension composed of ferrosilicon powder and improver with a specific proportion of high-density heavy medium, the problem of high-viscosity viscosity in high-density heavy medium sorting is solved, the separation accuracy and efficiency are improved, and the efficient separation of high-density minerals is achieved select.

CN115739377BActive Publication Date: 2025-01-03CENT SOUTH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211467168.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-01-03
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The high viscosity of high-density heavy medium suspension leads to the movement of mineral particles being disturbed by viscous resistance, and the sorting effect is poor. The prior art is difficult to improve the accuracy and efficiency of high-density heavy medium sorting.

Method used

A high-density heavy medium suspension consisting of weighting and improving agents, consisting of a specific proportion of ferrosilicon powder and improving agents (such as water glass, sodium pyrophosphate, sodium phosphate, natural polymer xanthan gum, polyacrylamide) Methods: reduce the viscosity of the suspension and improve the sorting accuracy and efficiency.

Benefits of technology

At the same density, the viscosity of the suspension decreases by 10% to 30%, the concentrate grade increases by 25% to 30%, the tailings grade decreases by 25% to 50%, and the concentrate recovery rate increases by more than 15%, achieving high-density re-introduction Improved accuracy and efficiency of sorting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
  • Figure DEST_PATH_IMAGE002
    Figure DEST_PATH_IMAGE002
  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
Patent Text Reader

Abstract

The invention relates to the technical field of high-density heavy medium separation, in particular to a high-density heavy medium suspension and a preparation method thereof, characterized in that the suspension comprises a weighting agent and an improving agent, the addition amount of the weighting agent is 2000-4000 Kg / (m3 of qualified heavy medium liquid), the addition amount of the improving agent is 0.4-1.0 Kg / (m3 of qualified heavy medium liquid), the weighting agent comprises 450-600 parts of 1# coarse-grained ferrosilicon powder, 150-300 parts of 2# fine-grained ferrosilicon powder, and 50-100 parts of 3# conventional ferrosilicon powder, and the improving agent comprises 3.5-10 parts of 1# improving agent and 1-2.5 parts of 2# improving agent. The invention has the advantages of simple formula, improved precision and efficiency of high-density heavy medium separation, low cost, good separation index, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-density heavy medium separation, and in particular to a high-density heavy medium suspension and a preparation method thereof, which has a simple formula, improves the precision and efficiency of high-density heavy medium separation, is low in cost, and has good separation indexes. Background Art

[0002] As we all know, with the increasing poverty, impurity and poor quality of mineral resources, the traditional grinding and flotation process will be difficult to adapt to the requirements of mineral processing. The gravity separation process can directly throw out 20% to 70% of the tailings at a suitable degree of dissociation. The rough concentrate after tailings is then put into the grinding and flotation process, which will greatly improve the flotation effect. At present, heavy medium separation is the most accurate separation method in gravity separation. The heavy medium separation method has become increasingly mature in the field of coal separation technology and has been widely used. In recent years, it has also been used in many applications in the field of mineral processing, such as barite, fluorite, lead-zinc ore, iron ore and other ores.

[0003] The heavy medium separation of high-density minerals has always been a difficult point in heavy medium separation. Since the separation density of heavy medium suspension determines the specific gravity limit of the separated ore, fine-grained ores with higher specific gravity require higher heavy medium separation density, which causes the viscosity of heavy medium suspension to increase sharply with the increase of solid volume, resulting in excessive interference from viscous resistance during the movement of mineral particles, making separation difficult and causing poor separation effect. At present, the separation of high-density minerals can only be completed by reducing the feed rate, but the accuracy and efficiency of heavy medium separation are still very low. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned deficiencies of the prior art and to provide a high-density heavy medium suspension and a preparation method thereof which has a simple formula, improves the accuracy and efficiency of high-density heavy medium separation, has low cost and has good separation indexes.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A high-density heavy medium suspension, characterized in that the suspension comprises a weighting agent and an improving agent, wherein the amount of the weighting agent added is 2000-4000 kg / (m 3 Qualified heavy medium), the amount of improver added is 0.4 ~1.0 Kg / (m 3Qualified heavy medium), the weight of the raw materials of the weighting material is composed of 450-600 parts of 1# coarse-grained ferrosilicon powder, 150-300 parts of 2# fine-grained ferrosilicon powder, and 50-100 parts of 3# conventional ferrosilicon powder. The weight of the raw materials of the improving agent is composed of 3.5-10 parts of 1# improving agent and 1-2.5 parts of 2# improving agent. The 1# improving agent is at least one of water glass, sodium pyrophosphate (Na4P2O7), and sodium phosphate (Na3PO4·12H2O). The 2# improving agent is at least one of natural polymer xanthan gum and polyacrylamide.

[0007] The 1# coarse-grained ferrosilicon powder of the present invention has a D50 of 40 μm to 55 μm, the 2# fine-grained ferrosilicon powder has a D50 of 8 μm to 17 μm, and the 3# conventional ferrosilicon powder has a D50 of 30 μm to 35 μm.

[0008] The 1# coarse-grained ferrosilicon powder and the 2# improving agent described in the present invention are composed of a mass ratio of 450-600:1-2.5.

[0009] The 2# fine-grained ferrosilicon powder and the 1# improving agent described in the present invention are composed of a mass ratio of 150-300:3.5-10.

[0010] A method for preparing a high-density heavy medium suspension: characterized in that the preparation method is as follows:

[0011] S1. respectively preparing qualified concentrations of 1# improver and 2# improver, wherein the 1# improver is at least one of water glass, sodium pyrophosphate (Na4P2O7), and sodium phosphate (Na3PO4·12H2O), and the 2# improver is at least one of natural polymer xanthan gum and polyacrylamide;

[0012] S2. Add 1# coarse-grained ferrosilicon powder into 1# mixing barrel and mix to form a suspension, and add the prepared 2# improving agent into 1# mixing barrel and stir to mix evenly to form a stable 1# heavy medium suspension, wherein the weight ratio of the added 1# coarse-grained ferrosilicon powder to the added weight of the 2# improving agent is 450-600:1-2.5;

[0013] S3. Add 2# fine-grained ferrosilicon powder to 2# combined medium barrel and mix to form a suspension, and add the prepared 1# improver to 2# combined medium barrel and stir, mix evenly to form a stable 2# heavy medium suspension, the weight of the added 2# fine-grained ferrosilicon powder and the weight of the added 2# improver are 150-300:3.5-10;

[0014] S4. Add 3# conventional ferrosilicon powder to 3# combined medium barrel and mix evenly to form a stable 3# heavy medium suspension;

[0015] S5. Add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension in equal parts into the mixing barrel, and add an appropriate proportion of water and stir until the components of the mixture are evenly mixed to form a qualified high-density heavy medium suspension;

[0016] The stirring speed of the mixing barrel described in the present invention is 200-800 r / min.

[0017] The configuration temperature of the improver solvent of the present invention is 55°C to 85°C.

[0018] Beneficial effects of the present invention: Compared with the prior art, the density of the sorted ore ranges from 2.60 to 3.35 g / cm 3 At the same time, the viscosity of the heavy medium suspension can be reduced by 10% to 30% at the same density, the concentrate grade can be increased by 25% to 30%, the tailings grade can be reduced by 25% to 50%, and the concentrate recovery rate can be increased by more than 15%. It has the advantages of simple formula, improved accuracy and efficiency of high-density heavy medium separation, low cost, and good separation indicators. DETAILED DESCRIPTION

[0019] The present invention is further described below:

[0020] In order to overcome the problems of serious structuring of high-density heavy medium suspension, high suspension viscosity, poor sorting effect, etc. in the prior art, the present invention provides a high-density heavy medium suspension and a preparation method, which can alleviate the structuring of the high-density heavy medium suspension, reduce the viscosity of the heavy medium suspension, and reduce the viscous resistance of mineral movement, thereby improving the sorting accuracy of heavy medium mineral separation. The specific scheme is as follows:

[0021] A high-density heavy medium suspension, characterized in that the suspension comprises a weighting agent and an improving agent, wherein the amount of the weighting agent added is 2000-4000 kg / (m 3 Qualified heavy medium), the amount of improver added is 0.4 ~1.0 Kg / (m 3 Qualified heavy medium), the weight of the raw materials of the weighting material is composed of 450-600 parts of 1# coarse-grained ferrosilicon powder, 150-300 parts of 2# fine-grained ferrosilicon powder, and 50-100 parts of 3# conventional ferrosilicon powder, and the weight of the raw materials of the improving agent is composed of 3.5-10 parts of 1# improving agent and 1-2.5 parts of 2# improving agent.

[0022] Furthermore, the D50 of the 1# coarse-grained ferrosilicon powder is 40 μm to 55 μm, the D50 of the 2# fine-grained ferrosilicon powder is 8 μm to 17 μm, and the D50 of the 3# conventional ferrosilicon powder is 30 μm to 35 μm.

[0023] Furthermore, the 1# improving agent is at least one of water glass, sodium pyrophosphate (Na4P2O7), and sodium phosphate (Na3PO4·12H2O).

[0024] Furthermore, the 2# improving agent is at least one of natural polymer xanthan gum and polyacrylamide.

[0025] Furthermore, the 1# coarse-grained ferrosilicon powder and the 2# improving agent are composed in a mass ratio of 450-600:1-2.5.

[0026] Furthermore, the 2# fine-grained ferrosilicon powder and the 1# improving agent are composed in a mass ratio of 150-300:3.5-10.

[0027] A method for preparing a high-density heavy medium suspension: characterized in that the preparation method is as follows:

[0028] S1. respectively preparing qualified concentrations of 1# improver and 2# improver, wherein the 1# improver is at least one of water glass, sodium pyrophosphate (Na4P2O7), and sodium phosphate (Na3PO4·12H2O), and the 2# improver is at least one of natural polymer xanthan gum and polyacrylamide;

[0029] S2. Add 1# coarse-grained ferrosilicon powder into 1# mixing barrel and mix to form a suspension, and add the prepared 2# improving agent into 1# mixing barrel and stir to mix evenly to form a stable 1# heavy medium suspension, wherein the weight ratio of the added 1# coarse-grained ferrosilicon powder to the added weight of the 2# improving agent is 450-600:1-2.5;

[0030] S3. Add 2# fine-grained ferrosilicon powder to 2# combined medium barrel and mix to form a suspension, and add the prepared 1# improver to 2# combined medium barrel and stir, mix evenly to form a stable 2# heavy medium suspension, the weight of the added 2# fine-grained ferrosilicon powder and the weight of the added 2# improver are 150-300:3.5-10;

[0031] S4. Add 3# conventional ferrosilicon powder to 3# combined medium barrel and mix evenly to form a stable 3# heavy medium suspension;

[0032] S5. Add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension in equal parts into the mixing barrel, and add an appropriate proportion of water and stir until the components of the mixture are evenly mixed to form a qualified high-density heavy medium suspension;

[0033] Furthermore, the stirring speed in the mixing barrel is 200-800r / min.

[0034] Furthermore, the configuration temperature of the improver solvent is 55° C. to 85° C. so that the improver can be dissolved quickly.

[0035] The above-mentioned controlled addition amount of weighting material is 2000-4000 Kg / (m3 qualified heavy medium liquid), and its purpose is to configure high-density heavy medium suspension, so as to ensure the effective separation of high-density ore by heavy medium cyclone.

[0036] The weight proportions of different components of weighting materials are controlled: 450-600 parts of 1# coarse-grained ferrosilicon powder, 150-300 parts of 2# fine-grained ferrosilicon powder, and 50-100 parts of 3# conventional ferrosilicon powder. The purpose is to configure the optimal particle size components of the heavy medium suspension according to the flow characteristics of the high-density heavy medium suspension, thereby reducing the solid phase volume concentration of the heavy medium suspension and reducing the viscosity of the heavy medium suspension, thereby overcoming the difficulty of structuring the high-density heavy medium suspension.

[0037] The composition of 1# coarse-grained ferrosilicon powder and 2# improver is controlled at a mass ratio of 450-600:1-2.5: the larger the weighting mass particle size, the smaller the viscosity of the configured heavy medium suspension, which helps to improve the structuring phenomenon of the high-density heavy medium suspension, but the coarse-grained heavy medium sedimentation rate is fast, and the surface edges and corners of the coarse particles are irregular, and the particle suspension is very unstable; and the added natural polymer xanthan gum or polyacrylamide and other 2# improvers, the carboxylate ions of which will bridge the 1# coarse-grained ferrosilicon powder particles to form a network structure, thereby increasing the stability of the entire system.

[0038] The composition of 2# fine-grained ferrosilicon powder and 1# improver is controlled at a mass ratio of 150-300:3.5-10: the weighting mass has a small particle size, and the configured heavy medium suspension has good stability, but high viscosity. It is necessary to add 1# improver such as water glass, sodium pyrophosphate (Na4P2O7), sodium phosphate (Na3PO4·12H2O), etc. to modify the surface of 2# fine-grained ferrosilicon powder, reduce the viscosity of the heavy medium suspension, reduce the viscous resistance of mineral movement, and ensure its stability, thereby improving the separation accuracy of heavy medium ore dressing.

[0039] Embodiment 1:

[0040] The WO3 grade of a tungsten mine in Hunan is about 0.240%. The heavy medium separation and collection operation is carried out. The raw ore is crushed and screened to 0.5-3 mm. In the first step, 1# coarse-grained ferrosilicon powder with a D50 of 40μm is added to the 1# combined medium barrel to form a heavy medium suspension. At the same time, the prepared natural polymer xanthan gum 2# improver is added to the 1# combined medium barrel and stirred. Mix well to form a stable 1# heavy medium suspension, in which the addition amounts of 1# coarse-grained ferrosilicon powder and natural polymer xanthan gum are 2000 Kg / m3 and 0.2 Kg / m3 respectively; in the second step, 2# fine-grained ferrosilicon powder with a D50 of 10μm is added to the 2# combined medium barrel to form a heavy medium suspension. At the same time, the prepared water glass 1# improver is added to the 2# combined medium barrel and stirred. Mix well to form a stable 2# heavy medium suspension, in which the addition amounts of 2# fine-grained ferrosilicon powder and water glass are 800 Kg / m3 and 0.7 Kg / m3; the third step is to add 3# conventional D50 30μm ferrosilicon powder into 3# combined medium barrel to form a heavy medium suspension, and the addition amount is 300Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add water in an appropriate proportion to stir until the components of the mixture are evenly mixed to form a qualified heavy medium suspension with a density of 2.92 g / cm3 and a viscosity of less than 30 mPa·s. The improved heavy medium suspension is pumped to the mixing barrel through the combined medium pump, and the desludging 0.5-3 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0041] The test results of this embodiment and the original heavy medium separation are shown in Table 1.

[0042] Table 1 Test results of this embodiment and traditional heavy medium separation

[0043]

[0044] From the above table, we can know that the density of tungsten ore in the composite medium is 2.92 g / cm 3 Under the conditions, the waste yield is about 65%, of which the grade of the original ore is 0.240%. The viscosity of the heavy medium liquid is reduced by 21.61% compared with the original process. The grade of the heavy medium separation concentrate is 0.472%, which is 25.53% higher than the concentrate grade of the original process; the tailings grade is 0.073%, which is 40% lower than the tailings grade of the original process; the WO3 recovery rate of the heavy medium operation is 72.56%, which is 17% higher than the WO3 recovery rate of the original process.

[0045] Example 2

[0046] The same tungsten ore in implementation case 1, with a raw ore WO3 grade of about 0.240%, was subjected to heavy medium separation and concentrating operation. The raw ore was crushed and screened to 0.5-3 mm. In the first step, 1# coarse-grained ferrosilicon powder with a D50 of 55μm was added to the 1# combined medium barrel to form a heavy medium suspension. At the same time, the prepared polyacrylamide 2# improver was added to the 1# combined medium barrel and stirred to form a stable 1# heavy medium suspension. The addition amounts of 1# coarse-grained ferrosilicon powder and polyacrylamide were 2500 Kg / m3 and 0.3 Kg / m3; the second step is to add 2# fine-grained ferrosilicon powder with D50 of 15μm into 2# mixing barrel to form a heavy medium suspension, and at the same time, add the prepared sodium phosphate (Na3PO4·12H2O) 1# improver into 2# mixing barrel and stir to form a stable 2# heavy medium suspension, wherein the addition amount of 2# fine-grained ferrosilicon powder and sodium phosphate (Na3PO4·12H2O) is 600 Kg / m3 and 0.7 Kg / m3 respectively; the third step is to add 3# conventional ferrosilicon powder with D50 of 30μm into 3# mixing barrel to form a heavy medium suspension, and the addition amount is 100Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add water in an appropriate proportion and stir until the components of the mixture are evenly mixed to form a density of 2.92 g / cm3 and a viscosity of less than 30 mPa·s qualified heavy medium suspension. The improved heavy medium suspension is pumped to the mixing tank through the mixing medium pump, and the desludged 0.5-3 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0047] The test results of this embodiment and the original heavy medium separation are shown in Table 2.

[0048] Table 2 Test results of this embodiment and traditional heavy medium separation

[0049]

[0050] It can be seen from the above table that: under the condition of combined medium density of 2.92 g / cm3, the waste yield of tungsten ore is about 65%, of which the grade of original ore is 0.240%. The viscosity of heavy medium liquid is reduced by 19.48% compared with the original process. The grade of heavy medium separation concentrate is 0.465%, which is 23.67% higher than that of the original process concentrate; the tailings grade is 0.072%, which is 35.71% lower than that of the original process tailings grade; the WO3 recovery rate of heavy medium operation is 67.12%, which is 11.56% higher than that of the original process WO3 recovery rate.

[0051] Example 3

[0052] The Pb+Zn grade of a lead-zinc mine in Guangxi is about 1.95%. The heavy medium separation and fine processing operation is carried out. The raw ore is crushed and screened to 0.5-5 mm. In the first step, 1# coarse-grained ferrosilicon powder with a D50 of 40μm is added to the 1# combined medium barrel to form a heavy medium suspension. At the same time, the prepared natural polymer xanthan gum 2# improver is added to the 1# combined medium barrel and stirred. Mix well to form a stable 1# heavy medium suspension, in which the addition amounts of 1# coarse-grained ferrosilicon powder and natural polymer xanthan gum are 1900 Kg / m3 and 0.2 Kg / m3 respectively; in the second step, 2# fine-grained ferrosilicon powder with a D50 of 10μm is added to the 2# combined medium barrel to form a heavy medium suspension. At the same time, the prepared water glass 1# improver is added to the 2# combined medium barrel and stirred. Mix well to form a stable 2# heavy medium suspension, in which the addition amounts of 2# fine-grained ferrosilicon powder and water glass are 700 Kg / m3 and 0.7 Kg / m3; the third step is to add 3# conventional D50 30μm ferrosilicon powder into 3# mixing barrel to form a heavy medium suspension, and the addition amount is 300Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add appropriate proportions of water to stir until the components of the mixture are evenly mixed to form a density of 2.75 g / cm 3 , and the viscosity is less than 25 mPa·s of qualified heavy medium suspension. The improved heavy medium suspension is pumped to the mixing tank through the mixing medium pump, and the desludging 0.5-5 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0053] The test results of this embodiment and the original heavy medium separation are shown in Table 3.

[0054] Table 3 Test results of this embodiment and traditional heavy medium separation

[0055]

[0056] It can be seen from the above table that: under the condition of combined medium density of 2.75g / cm3, the waste yield of the lead-zinc ore is about 65%, of which the Pb+Zn grade of the original ore is 1.95%. The viscosity of the heavy medium liquid is reduced by 19.11% compared with the original process, and the grade of the heavy medium separation concentrate is 5.21%, which is 4.00% higher than the concentrate grade of the original process; the tailings grade is 0.31%, which is 35.41% lower than the tailings grade of the original process; the Pb+Zn recovery rate of the heavy medium operation is 91.86%, which is 9.80% higher than the Pb+Zn recovery rate of the original process.

[0057] Example 4

[0058] The same lead-zinc ore as in Example 3, with a Pb+Zn grade of about 1.95%, was subjected to heavy medium separation and fine treatment. The ore was crushed and screened to 0.5-5 mm. In the first step, ferrosilicon powder with a D50 of 55 μm in the 1# coarse particle grade was added to the 1# medium barrel for mixing to form a heavy medium suspension. At the same time, the prepared polyacrylamide 2# improver was added to the 1# medium barrel for stirring and mixing to form a stable 1# heavy medium suspension. The addition amounts of ferrosilicon powder and polyacrylamide in the 1# coarse particle grade were 1800 Kg / m3 and 0.3 Kg / m3; the second step is to add 2# fine-grained ferrosilicon powder with D50 of 15μm into 2# mixing barrel to form a heavy medium suspension, and at the same time, add the prepared sodium phosphate (Na3PO4·12H2O) 1# improver into 2# mixing barrel and stir to form a stable 2# heavy medium suspension, wherein the addition amount of 2# fine-grained ferrosilicon powder and sodium phosphate (Na3PO4·12H2O) is 800 Kg / m3 and 0.7 Kg / m3 respectively; the third step is to add 3# conventional ferrosilicon powder with D50 of 30μm into 3# mixing barrel to form a heavy medium suspension, and the addition amount is 200Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add water in an appropriate proportion and stir until the components of the mixture are evenly mixed to form a density of 2.75 g / cm3 and a viscosity of less than 25 mPa·s qualified heavy medium suspension. The improved heavy medium suspension is pumped to the mixing tank through the mixing medium pump, and the desludged 0.5-5 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0059] The test results of this embodiment and the original heavy medium separation are shown in Table 4.

[0060] Table 4 Test results of this embodiment and traditional heavy medium separation

[0061]

[0062] It can be seen from the above table that: under the condition of combined medium density of 2.75g / cm3, the waste yield of the lead-zinc ore is about 65%, of which the Pb+Zn grade of the original ore is 1.95%. The viscosity of the heavy medium liquid is reduced by 14.25% compared with the original process, and the grade of the heavy medium separation concentrate is 5.26%, which is 5.00% higher than the concentrate grade of the original process; the tailings grade is 0.33%, which is 31.25% lower than the tailings grade of the original process; the Pb+Zn recovery rate of the heavy medium operation is 90.50%, which is 8.44% higher than the Pb+Zn recovery rate of the original process.

[0063] Embodiment 5:

[0064] The grade of Li2O in a spodumene ore in Xinjiang is about 1.65%. The heavy medium separation fine-grained ... Kg / m3 and 0.7 Kg / m3; the third step is to add 3# conventional D50 30μm ferrosilicon powder into 3# combined medium barrel to form a heavy medium suspension, and the addition amount is 200Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add water in an appropriate proportion to stir until the components of the mixture are evenly mixed to form a qualified heavy medium suspension with a density of 2.64 g / cm3 and a viscosity lower than 24 mPa·s. The improved heavy medium suspension is pumped to the mixing barrel through the combined medium pump, and the desludging 0.3-2 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0065] The test results of this embodiment and the original heavy medium separation are shown in Table 5.

[0066] Table 5 Test results of this embodiment and traditional heavy medium separation

[0067]

[0068] From the table above, we can see that the density of spodumene in the composite medium is 2.64 g / cm 3 Under the conditions, the waste yield is about 75%, of which the grade of the original ore is 1.65%. The viscosity of the heavy medium liquid is reduced by 17.88% compared with the original process. The grade of the heavy medium separation concentrate is 4.95%, which is 11.23% higher than that of the original process concentrate; the tailings grade is 0.51%, which is 21.53% lower than that of the original process tailings grade; the Li2O recovery rate of the heavy medium operation is 73.27%, which is 4.83% higher than that of the original process.

[0069] Example 6

[0070] The same spodumene mine of implementation case 5 was used for heavy medium separation and fine-grained ... Kg / m3 and 0.7 Kg / m3; the third step is to add 3# conventional D50 30μm ferrosilicon powder into 3# combined medium barrel to form a heavy medium suspension, and the addition amount is 200Kg / m3; the fourth step is to add the prepared 1# heavy medium suspension, 2# heavy medium suspension, and 3# heavy medium suspension into the mixing barrel in equal parts, and add water in an appropriate proportion to stir until the components of the mixture are evenly mixed to form a qualified heavy medium suspension with a density of 2.64 g / cm3 and a viscosity lower than 24 mPa·s. The improved heavy medium suspension is pumped to the mixing barrel through the combined medium pump, and the desludging 0.3-2 mm particle size selected raw ore is fully mixed with the suspension and pumped into the pressurized two-product heavy medium cyclone to separate the tailings and concentrate.

[0071] The test results of this embodiment and the original heavy medium separation are shown in Table 6.

[0072] Table 6 Test results of this embodiment and traditional heavy medium separation

[0073]

[0074] It can be seen from the above table that: under the condition of a combined medium density of 2.64 g / cm3, the waste yield of the spodumene is about 75%, of which the grade of the original ore is 1.65%. The viscosity of the heavy medium liquid of this invention is reduced by 19.13% compared with the original process; the grade of the heavy medium separation concentrate is 4.97%, which is 11.68% higher than the concentrate grade of the original process; the tailings grade is 0.53%, which is 18.46% lower than the tailings grade of the original process; the Li2O recovery rate of the heavy medium operation is 78.95%, which is 10.51% higher than the Li2O recovery rate of the original process.

[0075] As is known above, the D50 of 1# coarse-grained ferrosilicon powder is 40μm, the D50 of 2# fine-grained ferrosilicon powder is 10μm, the D50 of 3# conventional ferrosilicon powder is 30μm, the addition amount of 1# coarse-grained ferrosilicon powder to natural polymer xanthan gum is 2000:0.2, and the addition amount of 2# fine-grained ferrosilicon powder to water glass is 800:0.7. The configuration method of the high-density heavy medium suspension is the best. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-density heavy medium suspension, characterized in that The suspension includes a weighting agent and an improving agent, wherein the weighting agent is added in an amount of 2000-4000 kg / (m 3 Qualified heavy medium), the amount of improver added is 0.4 ~1.0 Kg / (m 3 Qualified heavy medium), the weight of the raw material composition of the weighting material is 450-600 parts of 1# coarse-grained ferrosilicon powder, 150-300 parts of 2# fine-grained ferrosilicon powder, 50-100 parts of 3# conventional ferrosilicon powder, the weight of the raw material composition of the improver is 3.5-10 parts of 1# improver, 1-2.5 parts of 2# improver, the 1# improver is water glass, sodium pyrophosphate (Na4P2O7), sodium phosphate (Na3PO4·12H2O) At least one of the above, the 2# improver is at least one of natural polymer xanthan gum and polyacrylamide, the 1# coarse-grained ferrosilicon powder has a D50 of 40μm to 55μm, the 2# fine-grained ferrosilicon powder has a D50 of 8μm to 17μm, the 3# conventional ferrosilicon powder has a D50 of 30μm to 35μm, the 1# coarse-grained ferrosilicon powder and the 2# improver are composed of a mass ratio of 450-600:1-2.5, the 2# fine-grained ferrosilicon powder and the 1# improver are composed of a mass ratio of 150-300:3.5-10, and the configuration method is as follows: S1. respectively preparing qualified concentrations of 1# improver and 2# improver, wherein the 1# improver is at least one of water glass, sodium pyrophosphate (Na4P2O7), and sodium phosphate (Na3PO4·12H2O), and the 2# improver is at least one of natural polymer xanthan gum and polyacrylamide; S2. Add 1# coarse-grained ferrosilicon powder into 1# mixing barrel and mix to form a suspension, and add the prepared 2# improving agent into 1# mixing barrel and stir to form a stable 1# heavy medium suspension, wherein the weight ratio of the 1# coarse-grained ferrosilicon powder to the 2# improving agent is 450-600:1-2.5; S3. Add 2# fine-grained ferrosilicon powder to 2# combined medium barrel and mix to form a suspension, and add the prepared 1# improving agent to 2# combined medium barrel and stir, mix evenly to form a stable 2# heavy medium suspension, the added weight of the 2# fine-grained ferrosilicon powder and the added weight of the 2# improving agent is 150-300:3.5-10; S4. Add 3# conventional ferrosilicon powder to 3# combined medium barrel and mix evenly to form a stable 3# heavy medium suspension; S5. Add the prepared 1# heavy medium suspension, 2# heavy medium suspension and 3# heavy medium suspension into the mixing barrel in equal parts, and add appropriate proportion of water to stir until all components of the mixture are evenly mixed to form a qualified high-density heavy medium suspension.

2. The method for preparing a high-density heavy medium suspension according to claim 1, characterized in that The stirring speed is 200-800 r / min.

3. The method for preparing a high-density heavy medium suspension according to claim 1, characterized in that The configuration temperature of the solvents of the 2# improver and the 1# improver is 55° C. to 85° C., so as to quickly dissolve the 2# improver and the 1# improver.